Modelling the kinetics of Listeria monocytogenes in refrigerated fresh beef under different packaging atmospheres - Saraiva, Cristina (2018)
The objective of this study was to model the fate of Listeria monocytogenes inoculated in beef at two concentrations (2.5 and 4.0 log CFU/g), packaged under air, vacuum and three modified atmospheres MAP: 70%O 2 /20%CO 2 /10%N 2 , 50%O 2 /40%CO 2 /10%N 2 and 30%O 2 /60%CO 2 /10%N 2 , and refrigerated at a normal temperature (4 °C) and at a mild abusive temperature (9 °C). The experimental design produced a total of 20 environmental conditions. An omnibus model based on the Weibull equation proved statistically that L. monocytogenes survives better in vacuum (VP) than in aerobic conditions, although without significant difference in its ability to survive in the temperature range between 4 °C and 9 °C. Furthermore, regardless of the refrigeration temperature, the presence of CO 2 in the package atmosphere exerted a bactericidal effect on L. monocytogenes cells, being approximately 1.5 log of reduction when storage time reached 10 days. Since the pathogen can survive in VP/MAP beef, there is a need of maintaining its numbers below 100 CFU/g before packaging by placing efforts on the implementation of control measures during processing.